Bibliography of Islamic Philosophy : Supplement - Daiber, Hans (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
Since the publication of the author´s BIBLIOGRAPHY OF ISLAMIC PHILOSOPHY in 1999 more than 3000 new books and articles in the field of Islamic philosophy, its Greek sources and its aftermath in European philosophy appeared and illustrate the increasing interest of the Islamic and the Western world. Philosophical thought as part of the Islamic culture became a medium in the dialogue between cultures and a tool for reflexion and methodology, which are indispensable for creativity and human behaviour. This supplement covers all new publications as far as they were available and could be included in the extensive index on authors, texts, translations and commentaries, and philosophical terms and concepts.